2009
DOI: 10.1371/journal.pgen.1000586
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CFTR in Skeletal Muscle Predisposes to Muscle Wasting and Diaphragm Muscle Pump Failure in Cystic Fibrosis Mice

Abstract: Cystic fibrosis (CF) patients often have reduced mass and strength of skeletal muscles, including the diaphragm, the primary muscle of respiration. Here we show that lack of the CF transmembrane conductance regulator (CFTR) plays an intrinsic role in skeletal muscle atrophy and dysfunction. In normal murine and human skeletal muscle, CFTR is expressed and co-localized with sarcoplasmic reticulum-associated proteins. CFTR–deficient myotubes exhibit augmented levels of intracellular calcium after KCl-induced dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 53 publications
(77 reference statements)
3
119
0
2
Order By: Relevance
“…These findings and our current data contrast with the typical localization of CFTR to the plasma membrane of polarized epithelial and serous cells (27,33,34). We further localized CFTR to the SR in ASM cells, a finding consistent with earlier reports of CFTR localization to the SR in skeletal muscle cells (41,42). CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells.…”
Section: /2supporting
confidence: 84%
See 1 more Smart Citation
“…These findings and our current data contrast with the typical localization of CFTR to the plasma membrane of polarized epithelial and serous cells (27,33,34). We further localized CFTR to the SR in ASM cells, a finding consistent with earlier reports of CFTR localization to the SR in skeletal muscle cells (41,42). CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells.…”
Section: /2supporting
confidence: 84%
“…CF disease manifestations are typically related to loss of CFTR function at the plasma membrane in epithelial cells. However, differing mechanisms of CFTR function in nonepithelial cells have been proposed, including intracellular vesicle acidification and SR calcium homeostasis in skeletal muscle (41)(42)(43)(44). The lack of localized plasma membrane CFTR staining in ASM is similar to that in other nonepithelial cells and suggests an intracellular function of CFTR in ASM.…”
Section: /2mentioning
confidence: 96%
“…Resting muscle ATP values have not been previously reported in the CF or PCD populations. Whether the decreased ATP levels we have observed is primary (6,7,30,31) or secondary to a defect in CFTR in the muscles of patients with CF cannot be directly determined from the current data. It is important to note that the biological consequence of this relatively small difference is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that exercise capacity and muscle function may be impaired in patients with CF and researchers have identified CF transmembrane conductance regulator (CFTR) mRNA expression in rodent skeletal muscle (5). A report has shown that an intrinsic alteration of function is linked to the absence of CFTR from skeletal muscle, leading to dysregulated calcium homeostasis, augmented inflammatory or atrophic gene expression signatures, and increased diaphragm muscle weakness (6). Our research team has recently demonstrated the expression of CFTR in human skeletal muscle (7).…”
mentioning
confidence: 99%
“…It has been shown that CFTR is expressed in the sarcoplasmic reticulum of skeletal muscle [15,16]. Deficiency of CFTR protein leads to elevated intracellular calcium levels and enhanced expression of inflammatory genes, which predisposes to muscle wasting in mice [15].…”
mentioning
confidence: 99%